Inexpensive thermochemical energy storage utilising additive enhanced limestone - Møller, K.T.; Ibrahim, A.; Buckley, Craig; Paskevicius, Mark (ROYAL SOC CHEMISTRY, 2020)
Energy storage is one of the key challenges in our society to enable a transition to renewable energy sources. The endothermic decomposition of limestone into lime and CO2is one of the most cost-effective energy storage systems but it significantly degrades on repeated energy cycling (to below 10% capacity). This study presents the first CaCO3system operating under physical conditions that mimic a real-life ‘thermal battery’ over an extended cycling life. These important results demonstrate that a thermal energy storage device based on CaCO3will be suitable for a range of applications,e.g.concentrated solar power plants, wind farms, photovoltaics, and excess grid energy. The operating temperature of 900 °C ensures a higher Carnot efficiency than state-of-the-art technologies at a fraction of the material cost. The capacity degradation of pure CaCO3as a function of calcination/carbonation cycling is overcome by the addition of either ZrO2(40 wt%) or Al2O3(20 wt%), which results in 500 energy storage cycles at over 80% capacity. The additives result in the formation of ternary compounds,e.g.CaZrO3and Ca5Al6O14, which restrict sintering and allow for the transmission of Ca2+and O2-ions to reaction sites.